2006
DOI: 10.1017/s0033291706008919
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in brain activation patterns during processing of positively and negatively valenced emotional words

Abstract: Our findings suggest gender-related neural responses to emotional stimuli and could contribute to the understanding of mechanisms underlying the gender disparity of neuropsychiatric diseases such as mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 34 publications
1
55
1
1
Order By: Relevance
“…One finding is the gender differences in brain activationpattern (fMRI) between women and men during processing of negatively valenced 52 words versus non-words (Hofer et al, 2007). Women showed greater activation in areas participating in understanding and expressing language and processing emotions and memories.…”
Section: Discussion Of the Main Findingsmentioning
confidence: 99%
“…One finding is the gender differences in brain activationpattern (fMRI) between women and men during processing of negatively valenced 52 words versus non-words (Hofer et al, 2007). Women showed greater activation in areas participating in understanding and expressing language and processing emotions and memories.…”
Section: Discussion Of the Main Findingsmentioning
confidence: 99%
“…While there is some significant overlap, men and women show several distinct regions of activation correlated with arousal ratings while viewing emotional images, including the post-central gyrus and hippocampus in women, and the putamen in men (Canli et al 2002). Similarly, during the processing of negatively valenced words, women show increased activity relative to men in the right putamen, right superior temporal gyrus, and left supramarginal gyrus (Hofer et al 2007). ERP studies have also shown differing response patterns to emotional material between men and women (Orozco and Ehlers 1998;Gasbarri et al 2007).…”
Section: The Affective Intensity Hypothesismentioning
confidence: 99%
“…Furthermore, we included only female participants in our study, limiting the generalizability of our results. On the other hand, the generally greater prevalence of social phobia in women 1 is reflected, and additional variance owing to existing differences in brain activation between men and women 64 has been avoided. Another limitation is that we did not control for menstrual cycle, which has been shown to influence brain activation.…”
Section: Limitationsmentioning
confidence: 99%